On Sūrah-Based Thematic Interpretation of the Qur’an: Genealogy and Methodology - Alfan Shidqon (STAI AL-FALAH CICALENGKA, 2023)
This article exploress sūrah-based thematic interpretation as a distinct method within Qur’anic exegesis, differing from the general thematic interpretation. While the latter compiles scattered verses under one theme, the former focuses on a single sūrah’s internal unity, structure, and message. Based on the work of Sāmir ʿAbd al-Raḥmān Rashwānī, this study explores its definition, historical development, and methodological principles. The genealogy of this approach traces back to classical scholars such as al-Bāqillānī, al-Rāzī, and al-Biqāʿī, and evolves through modern thinkers like al-Farāhī and Sayyid Quṭb. Methodologically, it involves five steps: analyzing the sūrah’s title, context of revelation (asbāb al-nuzūl), textual coherence (munāsabah), structural pillars (ʿamūd), and overall objectives (maqāṣid). Despite interpretive variation, this method offers a coherent framework for engaging the Qur’an’s message thematically; highlighting its relevance in contemporary discourse.